A dose of doubt: a qualitative study on placebo regulations - Richard, Mélina; Ganz, Manuela; Elger, Bernice S.; Gaab, Jens (Frontiers in Medicine, 2025)
IntroductionPlacebo use is common in primary care, yet ethical and legal concerns persist, and few qualitative studies have explored physicians’ views on placebo regulation.MethodsWe conducted semi-structured interviews with 10 primary care physicians from 2 German-speaking Swiss cantons to explore their definitions of placebos, usage in clinical practice, knowledge of existing regulations, and attitudes toward potential regulatory frameworks. Participants were recruited from a publicly available physician registry, yielding a 4.9% response rate.ResultsParticipants consistently reported using at least impure placebos in their practice, while references to the use of pure placebos were relatively uncommon. A distinction between pure and impure placebos emerged, with the latter generally viewed as more ethically acceptable. Risk-benefit evaluation was emphasized as the primary justification for placebo use. Most participants had not actively sought legal information, and knowledge about current regulations varied considerably. While clear support for specific regulation was rare, most participants did not perceive it as necessary, often citing distrust in regulatory systems or concerns that formal rules could restrict therapeutic flexibility. Expert bodies such as the Swiss Medical Association were mentioned as potential sources of guidance.DiscussionThe findings highlight a practice-oriented, risk-benefit-driven approach to placebo use, shaped by skepticism toward regulation and limited legal awareness. Despite frequent use, physicians operate in a legally ambiguous space and express limited demand for regulatory clarity, suggesting a need for targeted professional discourse rather than strict formal regulation.